Maternal parity modifies the association of birthweight polygenic score with fetal growth - Prabhavi Wijesiriwardhana; Tesfa Dejenie Habtewold; Guisong Wang; Jessica L. Gleason; Ronald J. Wapner; Katherine L. Grantz; Fasil Tekola-Ayele (Scientific Reports)
Abstract Low birthweight is more common among children born to nulliparas (women with no prior pregnancy lasting ≥20 weeks of gestation) compared to those born to multiparas (women with one or more prior pregnancies lasting ≥20 weeks). We investigated whether parity modifies the association of maternal genetic risk score (mGRS) of maternal birthweight-reducing genetic variants with fetal size and weekly growth pace (i.e., change in fetal size over a 1-week gestational age interval) at gestational weeks 10–40 in two multi-ancestral cohorts of pregnant women. mGRS, derived from previously identified birthweight-reducing maternal variants was tested for association with fetal size and weekly growth pace using linear regression adjusted for fetal sex and top 10 genetic principal components. Among nulliparas, but not among multiparas, higher birthweight-reducing mGRS was associated with lower fetal size and slower weekly growth pace as measured by fetal weight, humerus and femur lengths, and abdominal and head circumferences beginning from gestational week 11. The findings suggest that the maternal genetic factors target major physiological changes at the first pregnancy that get less profound with multi-parity. Considering parity as a biological variable may facilitate the precision of identifying sensitive intrauterine periods and interventions for pregnancy outcomes using genomics.